Multifunctional structure energy storage composite material and preparation method thereof

By using carbon fiber matrix and multi-stage conductive network in energy storage composite materials, combined with topological optimization and new resin-based electrolytes, the balance problem between existing materials in energy storage and mechanical strength is solved, and a high-performance structural energy storage composite material is achieved.

CN119905565AActive Publication Date: 2025-04-29SHENZHEN NO 1 FINE CHEM CO LTD

Patent Information

Application Number
CN202510129499.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-04-29
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

When improving energy storage performance, existing energy storage composite materials usually sacrifice mechanical strength and cannot meet both energy storage and load bearing requirements. They also have problems such as interface combination, insufficient ionic conductivity, complex manufacturing processes and insufficient environmental adaptability.

Method used

Using carbon fiber matrix as the mechanical bearing structure, a multi-stage conductive network is designed to coat conductive paste containing carbon nanotubes, graphene and MXene on the carbon fiber cloth. Through topological optimization and three-dimensional modeling, a special-shaped structure is designed, combined with a new resin-based electrolyte and vacuum-assisted resin transfer molding process, a multifunctional structure energy storage composite material is prepared.

Benefits of technology

The balance of energy storage performance and mechanical strength is achieved, the overall performance and service life of the material is improved, the ionic conductivity and interface bonding force are optimized, the preparation process is simplified, and the performance stability of the material in extreme environments is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a multifunctional structure energy storage composite material and a preparation method thereof, and belongs to the technical field of multifunctional composite materials. The carbon fiber reinforced matrix and the optimized special-shaped structure design are combined, excellent mechanical strength and rigidity are provided, so that high mechanical performance is achieved, meanwhile, due to application of the multi-stage conductive network and the electrolyte layer, the conductivity of the electrode and the utilization rate of active substances are remarkably improved, and excellent electrochemical performance is achieved. By introducing the multi-stage conductive network, the resin-based electrolyte and the optimized special-shaped structure design, the technical breakthrough is realized, the structural energy storage composite material with high performance (mechanical and electrochemical performance) is obtained, and the actual application requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of multifunctional composite materials, and in particular to a multifunctional structural energy storage composite material and a preparation method thereof. Background Art

[0002] With the development of new energy vehicles, aerospace and portable electronic devices, the demand for lightweight, high-strength and multifunctional materials is increasing. Traditional energy storage devices are usually separated from structural materials, which increases the weight and volume of the system. Energy storage composite materials are multifunctional materials that combine mechanical bearing capacity and energy storage functions, and have received widespread attention in the fields of new energy vehicles, aerospace and portable electronic devices.

[0003] Existing energy storage composite materials mainly include the following categories: 1. Lithium-ion battery composite materials: By integrating lithium-ion batteries into fiber-reinforced composite materials, a certain load-bearing capacity is achieved. Common designs include using carbon fiber as a structural skeleton and acting as an electrode material at the same time. 2. Supercapacitor composite materials: Active materials with high specific surface area (such as graphene and carbon nanotubes) are compounded with a polymer matrix to provide energy storage functions. Suitable for application scenarios that require fast charging and discharging. 3. Solid electrolyte composite materials: Combine ionic conductivity and mechanical strength for high-safety energy storage systems. Use a polymer matrix doped with inorganic fillers or ionic liquids to improve ionic conductivity and stability.

[0004] However, existing energy storage composite materials have the following problems: 1. Balance between energy storage and load-bearing performance: When improving energy storage performance, existing materials usually sacrifice mechanical strength and cannot meet the load-bearing requirements at the same time. For example, increasing the content of electrolyte or active substances will cause the matrix to become brittle. 2. Interface bonding problem: The interface bonding between the active material and the composite matrix is ​​poor, resulting in reduced energy storage efficiency or decreased mechanical properties. Especially in dynamic environments, interface separation is a common failure mode. 3. Insufficient ionic conductivity: Most energy storage composite materials have low ionic conductivity, which limits the charge and discharge rate. Uneven distribution of the conductive network or poor dispersion of ionic liquids / lithium salts are the main reasons. 4. Complex manufacturing process: Existing processes (such as lamination and vacuum infusion) are difficult to achieve large-area, integrated multifunctional composite material preparation. Bubbles or delamination defects are prone to occur during the preparation process, affecting the overall performance of the material. 5. Insufficient environmental adaptability: In extreme environments (such as high temperature and low temperature), the performance of energy storage composite materials decays greatly, making it difficult to meet application requirements.

[0005] Therefore, the development of structural energy storage composite materials that have both mechanical bearing and energy storage functions has important scientific significance and application value. Summary of the invention

[0006] The object of the present invention is to provide a multifunctional structural energy storage composite material and a preparation method thereof, wherein the multifunctional structural energy storage composite material integrates mechanical bearing and electrochemical energy storage functions.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a multifunctional structural energy storage composite material, comprising the following steps:

[0009] mixing carbon nanotubes, graphene, MXene and an organic solvent, and mixing the resulting suspension with a binder and a positive electrode active material to obtain a conductive slurry;

[0010] The carbon fiber cloth is subjected to plasma treatment to obtain a modified carbon fiber cloth;

[0011] The conductive slurry is electrospinned on the surface of the modified carbon fiber cloth to form a conductive coating, and then subjected to heat pressing to obtain a multi-level conductive network;

[0012] Mixing a lithium salt with an ionic liquid to obtain an ionic liquid electrolyte;

[0013] The ionic liquid electrolyte is mixed with a resin matrix, a functional polymer, a nanofiller and a curing agent to obtain a resin-based electrolyte precursor;

[0014] Using ANSYS software, topology optimization is performed according to the required mechanical strength and energy storage performance, and according to the optimization results, the multi-level conductive network is compounded with a resin-based electrolyte precursor to obtain a composite precursor;

[0015] According to the geometric shape obtained by topology optimization, a three-dimensional model of the special-shaped part is established by using SolidWorks, and the three-dimensional model of the special-shaped part is made into a mold by using a CNC processing method;

[0016] The positive electrode, electrolyte membrane and negative electrode are laid in sequence in a mold, and the composite precursor is injected into the mold by a vacuum-assisted resin transfer molding method, and then cured and molded to obtain a multifunctional structural energy storage composite material.

[0017] Preferably, the mass ratio of the carbon nanotubes, graphene and MXene is 1-3:1-3:1; the diameter of the carbon nanotubes is 10-20 nm, the length is 10-30 μm, and the conductivity is greater than 10 4 S / m; the graphene is a single-layer redox graphene with a thickness of <1nm and a side length of 5 to 10μm; the MXene is Ti3C2T x The thickness of the MXene is <2 nm and the sheet diameter is 1 to 5 μm.

[0018] Preferably, the binder is polyvinylidene fluoride, and the molecular weight of the polyvinylidene fluoride is 450,000; the power of the plasma treatment is 80 to 120 W, and the time is 5 to 10 minutes.

[0019] Preferably, the electrospinning conditions include: voltage 10-15 kV; collection distance 10-15 cm; slurry flow rate 0.1-0.2 mL / min;

[0020] The temperature of the hot pressing treatment is 130-160° C., the pressure is 10-15 MPa, and the time is 2-5 hours.

[0021] Preferably, the ionic liquid includes 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide; the lithium salt includes lithium hexafluorophosphate; and the mass ratio of the lithium salt to the ionic liquid is 1:5-15.

[0022] Preferably, the resin matrix includes bisphenol F epoxy resin; the functional polymer includes sulfonated polyetheretherketone; the nanofiller includes nanosilica; and the curing agent includes polyetheramine curing agent D230 or dicyandiamide.

[0023] Preferably, the mass of the functional polymer is 3-6% of the mass of the resin matrix, the mass of the nanofiller is 1-3% of the mass of the resin matrix; the mass ratio of the resin matrix to the curing agent is 100:30-50; the mass ratio of the ionic liquid to the resin matrix is ​​0.5-1:1.

[0024] Preferably, when the curing agent is polyetheramine curing agent D230, the curing molding includes: curing at 80-100° C. for 4 hours, and then curing at 120-150° C. for 2 hours.

[0025] Preferably, when the curing agent is dicyandiamide, a modified imidazole accelerator is added, and the mass of the modified imidazole accelerator is 1.5-3% of the mass of the resin matrix; the curing molding is: curing at 120-130° C. for 30 minutes.

[0026] The present invention provides a multifunctional structural energy storage composite material prepared by the preparation method described in the above technical solution.

[0027] The present invention provides a method for preparing a multifunctional structural energy storage composite material, using a carbon fiber matrix as a mechanical bearing structure to provide high strength and stiffness; designing a multi-level conductive network, coating a conductive slurry containing carbon nanotubes, graphene and MXene on a carbon fiber cloth, constructing a multi-level conductive network, and improving the conductivity and energy storage performance of the electrode; introducing functional polymers and nanofillers into the resin matrix to enhance ion conductivity and mechanical properties; optimizing the design of the special-shaped structure, and designing special-shaped parts that meet specific mechanical and energy storage requirements through topological optimization and three-dimensional modeling. The present invention adopts a carbon fiber reinforced matrix combined with an optimized special-shaped structure design to provide excellent mechanical strength and stiffness, thereby achieving high mechanical properties. At the same time, the application of a multi-level conductive network and an electrolyte layer significantly improves the conductivity of the electrode and the utilization rate of active substances, thereby achieving excellent electrochemical performance. The present invention achieves a technological breakthrough by introducing a multi-level conductive network, a new resin-based electrolyte and an optimized special-shaped structure design, and obtains a high-performance (mechanical and electrochemical performance) structural energy storage composite material to meet practical application requirements.

[0028] The solution of the present invention has the following advantages:

[0029] 1. Multifunctional balance: while improving energy storage performance (such as ionic conductivity and energy storage density), it maintains high strength and toughness to meet mechanical load-bearing requirements.

[0030] 2. Enhanced interface bonding strength: Optimize the interface compatibility between the positive electrode active material and the matrix, and improve the overall performance and service life of the material.

[0031] 3. Optimization of ionic conductivity: Improve the ion mobility of the electrolyte by introducing ionic liquids, lithium salts and multi-level conductive networks.

[0032] 4. Improvement of preparation process: Design efficient and low-defect preparation processes (such as vacuum infusion combined with rapid curing system) to achieve uniform distribution and large-area preparation.

[0033] 5. Improved environmental adaptability: Through material design and optimization, composite materials can maintain stable performance in a wide temperature range and complex environment.

[0034] The present invention can adopt bio-based green and environmentally friendly epoxy resin and recyclable technology to reduce environmental impact and improve the environmental performance and sustainability of the material. DETAILED DESCRIPTION

[0035] In the present invention, unless otherwise specified, the raw materials or reagents used are commercially available products well known in the art.

[0036] The present invention provides a method for preparing a multifunctional structural energy storage composite material, comprising the following steps:

[0037] mixing carbon nanotubes, graphene, MXene and an organic solvent, and mixing the resulting suspension with a binder and a positive electrode active material to obtain a conductive slurry;

[0038] The carbon fiber cloth is subjected to plasma treatment to obtain a modified carbon fiber cloth;

[0039] The conductive slurry is electrospinned on the surface of the modified carbon fiber cloth to form a conductive coating, and then subjected to heat pressing to obtain a multi-level conductive network;

[0040] Mixing a lithium salt with an ionic liquid to obtain an ionic liquid electrolyte;

[0041] The ionic liquid electrolyte is mixed with a resin matrix, a functional polymer, a nanofiller and a curing agent to obtain a resin-based electrolyte precursor;

[0042] Using ANSYS software, topology optimization is performed according to the required mechanical strength and energy storage performance, and according to the optimization results, the multi-level conductive network is compounded with a resin-based electrolyte precursor to obtain a composite precursor;

[0043] According to the geometric shape obtained by topology optimization, a three-dimensional model of the special-shaped part is established by using SolidWorks, and the three-dimensional model of the special-shaped part is made into a mold by using a CNC processing method;

[0044] The positive electrode, electrolyte membrane and negative electrode are laid in sequence in a mold, and the composite precursor is injected into the mold by a vacuum-assisted resin transfer molding method, and then cured and molded to obtain a multifunctional structural energy storage composite material.

[0045] In the present invention, the mass ratio of the carbon nanotubes, graphene and MXene is preferably 1-3:1-3:1, more preferably 2:2:1; the diameter of the carbon nanotubes is preferably 10-20 nm, the length is preferably 10-30 μm, and the conductivity is preferably>10 4 S / m; the graphene is a single-layer redox graphene with a thickness of <1nm and a side length of 5 to 10μm; the MXene is preferably Ti3C2T x The thickness of the MXene is preferably <2 nm, and the sheet diameter is preferably 1 to 5 μm.

[0046] In the present invention, the organic solvent is preferably N-methylpyrrolidone (NMP); the present invention has no special limitation on the amount of the organic solvent, and the amount can be adjusted according to the dosage known in the art to ensure sufficient mixing of the materials.

[0047] In the present invention, the carbon nanotubes, graphene and MXene are preferably added to an organic solvent and dispersed for 30 minutes using an ultrasonic disperser to form a uniform suspension.

[0048] In the present invention, the binder is preferably polyvinylidene fluoride, and the molecular weight of the polyvinylidene fluoride is preferably 450,000; the mass proportion of the binder in the conductive paste is preferably 5-10%, and more preferably 5-8%. In the present invention, PVDF is preferably dissolved in NMP to form a binder solution with a concentration of 10wt%, which is added to the suspension.

[0049] In the present invention, the positive electrode active material preferably includes lithium iron phosphate, lithium iron phosphate, lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium nickel cobalt manganese oxide (LiNixCoyMnO2, NCM / NMC), lithium nickel cobalt aluminum oxide (LiNi x Co y AlO2, NCA), lithium-rich manganese-based positive electrode materials (Li-richMn-based oxide), phosphate-based positive electrode materials (LiMnPO4, LiCoPO4) or composite doped positive electrode materials (Li2FeSiO4, LiVPO4F); the mass of the positive electrode active material is preferably 75-85wt% of the suspension, more preferably 80wt%. The present invention has no special limitation on the source of the positive electrode active material, and any corresponding positive electrode active material known in the art can be used.

[0050] The present invention has no particular limitation on the specification and source of the carbon fiber cloth, and any commercially available product known in the art may be used.

[0051] In the present invention, the power of the plasma treatment is preferably 80 to 120 W, more preferably 90 to 100 W, and the time is preferably 5 to 10 min, more preferably 5 to 8 min. The present invention has no special restrictions on the equipment and other conditions of the plasma treatment, and it can be carried out according to the process known in the art.

[0052] In the present invention, the conditions for electrospinning preferably include: voltage 10-15 kV; collection distance 10-15 cm; slurry flow rate 0.1-0.2 mL / min; the voltage is more preferably 12-15 kV; the collection distance is more preferably 12 cm; the slurry flow rate is more preferably 0.1-0.15 mL / min.

[0053] In the present invention, the thickness of the conductive coating is preferably 15 to 30 μm, more preferably 20 μm.

[0054] After the electrospinning is completed, the present invention preferably carries out drying in a vacuum drying oven at 80° C. for 6 hours to remove the solvent.

[0055] The present invention has no special limitation on the thickness of the conductive coating, which can be adjusted according to actual needs; in the embodiment of the present invention, it is specifically 20 μm.

[0056] In the present invention, the temperature of the hot pressing treatment is preferably 130-160°C, more preferably 150°C, the pressure is preferably 10-15MPa, more preferably 10-12MPa, and the time is preferably 2-5h, more preferably 2-3h. The present invention enhances the bonding strength between the conductive coating and the carbon fiber cloth by hot pressing.

[0057] In the present invention, carbon nanotubes are uniformly dispersed in the slurry in the form of single-walled (SWCNTs) or multi-walled (MWCNTs), and form an interwoven nano-network, which is mainly distributed on the surface and pores of the carbon fiber cloth and cross-linked with other conductive materials; as a bridge for electron transmission, the high aspect ratio and excellent conductivity of CNTs construct a fast electron transmission network; after the slurry is cured, CNTs improve the mechanical properties of the coating through physical embedding and chemical bonding; provide additional specific surface area, improve energy storage performance and electrochemical activity. Graphene is dispersed in a single-layer or few-layer structure, uniformly attached to the surface of the carbon fiber cloth and between the CNTs network, with a layered lamellae structure, part of the graphene interacts with the carbon fiber in a π-π manner, and is stably bonded, which can improve the two-dimensional conductive network, and the high conductivity of graphene (~10 5 S / m) and CNTs work together to build a multi-level conductive network to reduce the electron transmission path; the sheet structure effectively covers the fiber surface and improves the interface bonding strength between the slurry and the carbon fiber cloth; its high specific surface area (~2600m 2 / g) provides active sites for electrochemical reactions and enhances the performance of capacitor energy storage. MXene is distributed in the form of nanosheets or sheet stacks, embedded in CNTs and graphene networks, and partially covers the surface of carbon fibers; the surface of the sheet has hydrophilic functional groups (such as -OH, -F, -Cl), which interact with the matrix and other conductive materials; provides ion conduction channels: hydrophilic functional groups and interlayer gaps provide low-resistance paths for ion migration, improving ion conductivity; the sheet structure improves energy storage capacity through pseudocapacitance effects (such as surface redox reactions); flaky MXene fills the network gaps, enhances the stability of the coating structure, reduces internal resistance, and improves interface stability.

[0058] The synergistic distribution and function of carbon nanotubes, graphene and MXene in the present invention:

[0059] Hierarchical network structure: CNTs form a one-dimensional conductive skeleton, graphene constructs a two-dimensional conductive network, and MXene provides the combination point of two-dimensional conductivity and ionic conductivity. The three work together to build a multi-level conductive network.

[0060] Distribution characteristics: CNTs penetrate the coating to form a continuous conductive path. Graphene is evenly distributed between CNTs and on the surface of carbon fiber cloth, providing a large-area electron transmission path. MXene: embedded in the network, forming an intersection for electron and ion conduction.

[0061] The three materials work together to build a high-speed electron transmission channel, forming a multi-level conductive network and improving electron mobility. The high specific surface area and active sites of CNTs, graphene and MXene increase the double-layer capacitance and pseudo-capacitance effect of the electrode, and improve energy storage performance. Flake graphene and MXene fill the gaps, improving the bonding strength between the coating and the carbon fiber cloth and the long-term stability of the interface.

[0062] Electronic transport performance: The electronic conductivity of the multi-level conductive network is significantly improved, reaching 2.5×105S / m; Ionic conductivity performance: The ion mobility of MXene is enhanced, which improves the overall electrode ion conductivity. Energy storage performance: The specific capacity of the electrode reaches 200F / g, which is more than 30% higher than that of traditional coatings. Mechanical properties: The elongation at break and tensile strength of the coating are significantly improved. This distribution and state design of carbon nanotubes, graphene, and MXene in the present invention ensures the high efficiency of the multi-level conductive network, while giving the composite material excellent energy storage performance and mechanical stability.

[0063] The present invention mixes lithium salt with ionic liquid to obtain ionic liquid electrolyte; and mixes the ionic liquid electrolyte with a resin matrix, a functional polymer, a nano filler and a curing agent to obtain a resin-based electrolyte precursor.

[0064] In the present invention, the ionic liquid preferably includes 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI); the lithium salt preferably includes lithium hexafluorophosphate; the mass ratio of the lithium salt to the ionic liquid is preferably 1:5-15, more preferably 1:10.

[0065] In the present invention, the resin matrix preferably includes bisphenol F epoxy resin; the mass ratio of the ionic liquid to the resin matrix is ​​preferably 0.5 to 1:1, more preferably 0.8:1.

[0066] In the present invention, the functional polymer preferably includes sulfonated polyetheretherketone; the mass of the functional polymer is preferably 3-6% of the mass of the resin matrix; as a preferred embodiment of the present invention, the functional polymer preferably also includes polylactic acid (PLA), and the mass of PLA is preferably 3-5% of the mass of the resin matrix.

[0067] In the present invention, the nano filler preferably includes nano silicon dioxide; the mass of the nano filler is preferably 1 to 3% of the mass of the resin matrix.

[0068] In the present invention, the curing agent preferably includes polyetheramine curing agent D230 or dicyandiamide; the mass ratio of the resin matrix to the curing agent is preferably 100:30-50, more preferably 100:35-40.

[0069] The present invention preferably dissolves the lithium salt in the ionic liquid and stirs until it is completely dissolved to obtain an ionic liquid electrolyte; adds the functional polymer and the nanofiller to the resin matrix, stirs evenly, adds the ionic liquid electrolyte, continues stirring for 1 hour, adds the curing agent, stirs and mixes, and obtains a resin-based electrolyte precursor.

[0070] In the present invention, when the curing agent is polyetheramine curing agent D230, the curing molding preferably includes: curing at 80-100°C for 4 hours and then curing at 120-150°C for 2 hours. When the curing agent is dicyandiamide, it also includes adding a modified imidazole accelerator, the mass of the modified imidazole accelerator is preferably 1.5-3% of the mass of the resin matrix, more preferably 2%; the curing molding is preferably: curing at 120-130°C for 30 minutes.

[0071] When the curing agent is dicyandiamide, the present invention can achieve rapid curing.

[0072] The present invention has no particular limitation on the specific process of topology optimization using ANSYS software according to the required mechanical strength and energy storage performance, and the topology optimization can be performed using a process well known in the art.

[0073] The roles of topological optimization in the present invention include: 1. Maximizing mechanical strength: By adjusting the material distribution and geometric shape, ensure that the composite material has sufficient mechanical properties to cope with complex loads. 2. Improving energy storage performance: Optimizing the distribution of multi-level conductive networks to minimize the transmission path of electrons and ions and improve energy storage efficiency. 3. Balancing performance and weight: While meeting the requirements of mechanical strength and energy storage performance, lightweight design is achieved, which is suitable for new energy vehicles and aerospace fields. 4. Adapting to the needs of special-shaped parts: In response to the design requirements of complex shapes, ensure the consistency of material properties in various directions and regions.

[0074] In the present invention, the topology optimization step preferably includes:

[0075] 1. Initial model construction: According to actual needs, define the geometric boundaries, dimensions and functional areas (such as load-bearing area and energy storage area) of special-shaped parts.

[0076] Setting of material properties: Input the material parameters of the multi-level conductive network (CNTs, graphene, MXene) and resin-based electrolyte precursor, including: elastic modulus, Poisson's ratio (mechanical properties), conductivity, ionic conductivity (energy storage performance), density (weight).

[0077] 2. The benchmark of topology optimization, the optimization target is based on the following indicators:

[0078] 1) Mechanical performance benchmark:

[0079] Maximize mechanical strength, with target values ​​of tensile strength ≥50MPa and compressive strength ≥100MPa.

[0080] Minimize structural deformation and ensure that the deformation is controlled within 1%.

[0081] 2) Energy storage performance benchmark:

[0082] Improve ionic conductivity, the target value is ≥1.8×10 -3 S / cm.

[0083] Optimize the conductive network of the electrode to ensure that the electronic conductivity is ≥2.5×10 5 S / m.

[0084] 3) Weight optimization benchmark:

[0085] While meeting the above performance indicators, the amount of material used is minimized to achieve lightweight design.

[0086] 3. Optimization process

[0087] Step 1: Initial material distribution:

[0088] Set the material filling rate (usually 30% to 80%) as the initial condition for the optimization calculation.

[0089] Step 2: Setting constraints:

[0090] Mechanical constraints: Apply fixed boundary conditions and external loads to simulate the actual usage environment.

[0091] Energy storage constraints: Set the path distribution of the conductive network and electrolyte to ensure that the transmission paths of ions and electrons are connected.

[0092] Step 3: Iterative calculation:

[0093] Using the ANSYS topology optimization module, through iterative solving, the inefficient material areas are gradually eliminated while maintaining the material distribution in key functional areas.

[0094] Step 4: Result analysis:

[0095] Generate optimized material distribution maps to determine the optimal geometry of the composite material and the distribution location of the functional materials.

[0096] According to the optimization result, the present invention compounds the multi-level conductive network with a resin-based electrolyte precursor in proportion to obtain a composite precursor.

[0097] In the present invention, the mass ratio of the multi-level conductive network to the resin-based electrolyte precursor is preferably 15:85 to 25:75.

[0098] In the present invention, the method for compositeing the multi-level conductive network and the resin-based electrolyte precursor is preferably a vacuum infusion process (VARTM): the multi-level conductive network (containing CNTs / graphene / MXene coating) is laid in a mold, and the resin-based electrolyte precursor is injected after vacuuming to penetrate and fill the pores of the multi-level conductive network skeleton, and the temperature (20-80°C) and vacuum degree (50-500mbar) are maintained, and after curing at 120-160°C for 0.5-5h, a composite precursor is obtained.

[0099] As another scheme of the present invention, the method for composite the multi-level conductive network with the resin-based electrolyte precursor preferably adopts a direct mixing-stirring method: the multi-level conductive network is mixed with the resin-based electrolyte precursor in proportion, mechanical stirring or ultrasonic dispersion is used to obtain a uniform composite precursor, and then vacuum degassing and curing are performed.

[0100] According to the geometric shape obtained by topological optimization, the present invention uses SolidWorks to establish a three-dimensional model of a special-shaped part, and uses a CNC processing method to make the three-dimensional model of the special-shaped part into a mold; the positive electrode, the electrolyte membrane, and the negative electrode are laid in the mold in sequence, and a vacuum-assisted resin transfer molding method is used to inject the composite precursor into the mold, and then solidification is performed to obtain a multifunctional structural energy storage composite material.

[0101] The present invention has no special limitation on the material of the mold, and any mold material known in the art may be used; in the embodiment of the present invention, the mold is specifically made of aluminum alloy.

[0102] The present invention has no special limitation on the positive electrode, electrolyte membrane and negative electrode, and corresponding materials well known in the art can be used; specifically, it is preferred to lay a layer of electrolyte membrane between the carbon fiber cloth containing the positive electrode material and the carbon fiber cloth containing the negative electrode material, and add collectors to the positive and negative electrode material layers respectively to form the positive and negative electrodes of the battery, and the electrolyte membrane is preferably glass fiber cloth, aramid fiber cloth or polyester fiber cloth.

[0103] The mechanical properties of the composite material after optimization by the present invention are improved: the tensile strength is increased by 20%, and the compressive strength is increased by 25%. The energy storage performance is improved: the ionic conductivity is increased to 1.9×10 -3 S / cm, and the electronic conductivity reaches 2.8×10 5 S / m. Weight reduction: material usage is reduced by 15%, achieving lightweight design. Through topological optimization, not only the requirements of mechanical strength and energy storage performance of multifunctional composite materials are met, but also the utilization efficiency and environmental adaptability of materials are improved, providing a scientific basis for the design and manufacture of complex special-shaped parts.

[0104] The present invention provides a multifunctional structural energy storage composite material prepared by the preparation method described in the above technical solution.

[0105] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0106] Example 1

[0107] 1. Preparation of multi-level conductive network

[0108] 1) Material selection

[0109] Carbon fiber cloth: T700 grade carbon fiber, fiber diameter 7μm, density 1.8g / cm 3 , produced by Toray Industries.

[0110] Positive electrode active material: lithium iron phosphate (LiFePO4), particle size 300nm, specific capacity 170mAh / g, provided by Xiamen Junshi Energy Technology Co., Ltd.

[0111] Negative electrode active material: artificial graphite, particle size 2 μm, specific capacity 360 mAh / g, provided by Shenzhen BTR New Energy Materials Co., Ltd.

[0112] Conductive additives:

[0113] Multi-walled carbon nanotubes (MWCNTs): diameter 10–20 nm, length 10-30 μm, conductivity >10 4 S / m, Qianrenhe Material Technology Co., Ltd.

[0114] Graphene: Single-layer redox graphene, thickness <1nm, side length 5-10μm, Sixth Element Materials Technology Co., Ltd.

[0115] MXene (Ti3C2Tx): thickness <2nm, flake diameter 1-5μm, synthesized by Ningbo Institute of Materials.

[0116] Binder: polyvinylidene fluoride (PVDF), Arkema.

[0117] Solvent: N-methylpyrrolidone (NMP), analytical grade.

[0118] 2) Preparation of electrode slurry

[0119] Conductive agent mixing: MWCNTs, graphene and MXene were mixed in a mass ratio of 2:2:1, added into NMP solvent, and ultrasonically dispersed for 30 minutes to form a uniform suspension.

[0120] Slurry preparation:

[0121] The binder PVDF was dissolved in NMP to form a 10 wt % PVDF solution.

[0122] The positive electrode active material LiFePO4 was added to the conductive agent suspension with a solid content of 80 wt %, and stirred evenly. The PVDF solution was added and dispersed at high speed for 5 minutes to obtain a uniform conductive slurry.

[0123] 3) Electrospinning coating process

[0124] The carbon fiber cloth was subjected to plasma treatment, and the treatment parameters were: power 100 W, time 5 min, and gas was oxygen;

[0125] The conductive slurry was injected into the electrospinning equipment with the spinning parameters of: voltage 15 kV, receiving distance 12 cm, flow rate 0.1 mL / min, to form a uniform conductive coating on the plasma-treated carbon fiber cloth with a coating thickness of 20 μm.

[0126] 4) Drying and heat treatment

[0127] Drying: Dry in a vacuum drying oven at 80°C for 6 h.

[0128] Hot pressing treatment: The dried material was hot pressed at 150°C, a pressure of 10 MPa, and a time of 2 h to obtain a multi-level conductive network.

[0129] 2. Preparation of resin-based electrolyte precursor

[0130] 1) Material selection

[0131] Resin matrix: bisphenol F epoxy resin EMTE170, epoxy equivalent EEW165~175g / eq, Shandong Aimonte New Materials Co., Ltd.

[0132] Curing agent: polyetheramine curing agent D230, Huntsman.

[0133] Functional polymer: Sulfonated polyetheretherketone (SPEEK), sulfonation degree 50%, Shanghai Research Institute of Chemical Industry.

[0134] Nanofiller: Nano silicon dioxide (SiO2), particle size 20 nm, Jiangsu Hailong Nanotechnology Co., Ltd.

[0135] Ionic liquid: 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt (EMIM-TFSI), purity 99%, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0136] Lithium salt: lithium hexafluorophosphate (LiPF6), battery grade.

[0137] 2) Preparation steps

[0138] Ionic liquid electrolyte preparation:

[0139] Dissolve LiPF6 in EMIM-TFSI at a mass ratio of 1:10 and stir until completely dissolved to obtain an ionic liquid electrolyte;

[0140] Preparation of resin-based electrolyte precursor:

[0141] Add SPEEK and nano-SiO2 to E51 at 5% and 2% of the resin mass, stir evenly, add ionic liquid electrolyte, the mass ratio of ionic liquid to resin is 0.8:1, continue stirring for 1 hour, add curing agent D230, the mass ratio of resin to curing agent is 100:35, mix evenly, and obtain a resin-based electrolyte precursor.

[0142] 3. Structural design and preparation of special-shaped parts

[0143] 1) Structural design

[0144] Topology Optimization:

[0145] Using ANSYS software, the composite material was topologically optimized to maximize mechanical strength and energy storage performance. According to the optimization results, the multi-level conductive network (including CNTs / graphene / MXene coating) was laid in the mold, the temperature was maintained at 35°C, the vacuum degree was 200mbar, and the resin-based electrolyte precursor was injected after evacuation. The multi-level conductive network and the resin-based electrolyte precursor were cured at 140°C for 2h in a mass ratio of 20:80 to obtain a composite precursor.

[0146] 3D modeling: Based on the geometric shape obtained by topology optimization, SolidWorks is used to build a 3D model of special-shaped parts with complex surfaces and reinforcing rib structures.

[0147] 2) Preparation process

[0148] Mould making: According to the 3D model of special-shaped parts, the mould is made by CNC machining, and the material is aluminum alloy;

[0149] Lamination assembly: Lay a layer of aramid fiber cloth between the carbon fiber cloth containing the positive electrode material and the carbon fiber cloth containing the negative electrode material, add collectors to the positive and negative electrode material layers respectively to form the positive and negative electrodes of the battery, and lay the positive electrode, aramid fiber cloth, and negative electrode in the mold in order.

[0150] Resin infusion: using a vacuum assisted resin transfer molding (VARTM) process, the composite precursor is injected into the mold under vacuum to prevent the generation of bubbles;

[0151] Curing: Curing at 80°C for 4 h, and then post-curing at 120°C for 2 h to obtain a multifunctional structural energy storage composite material.

[0152] Example 2

[0153] The only difference from Example 1 is that dicyandiamide and modified imidazole accelerator (fast curing system) are used in the resin-based electrolyte precursor, the addition amount of dicyandiamide ("Dyhard 100S" series produced by Evonik Industries) is 5% of the resin mass, and the modified imidazole accelerator (produced by Shikoku Chemicals, Japan) is 1. series, Curezol 2MZ-A) is added in an amount of 2% of the resin mass;

[0154] Curing procedure: Curing at 120°C for 30 minutes.

[0155] Compared with the traditional bisphenol F-polyetheramine system of "80°C curing for 4h + 120°C post-curing for 2h" adopted in Example 1, Example 2 can complete the curing at 120°C in only 30 minutes.

[0156] Curing time: Experimental monitoring shows that when the temperature is raised to 120°C from the beginning of injection molding and maintained for 30 minutes, the curing degree of the whole material can be ≥ 95%. Compared with Example 1, the overall production cycle is shortened by 30%.

[0157] Mechanical properties: Since the modified imidazole accelerator makes the curing more thorough, the cross-linking density of the material is higher, and the tensile strength and bonding properties of the composite material can still be maintained at a high level (not much different from Example 1, the tensile strength is slightly improved by 3-5%).

[0158] Energy storage performance: The fast curing system did not cause significant damage to the ionic liquid and the conductive network; the ionic conductivity measured at room temperature was 1.4×10 -3 S / cm, electronic conductivity 2.6×10 5 S / m is equivalent to that in Example 1.

[0159] Example 2 introduces a dicyandiamide latent curing agent and a modified imidazole accelerator, which greatly shortens the curing time and improves production efficiency, while the material properties remain excellent and can meet large-scale or rapid production needs. This solution is particularly suitable for aerospace or automotive production lines that have strict cycle requirements.

[0160] Example 3

[0161] Environmental protection and recyclability research

[0162] The difference between this embodiment and embodiment 1 is only that:

[0163] 1) Use bio-based epoxy resin: replace 30% of E51 epoxy resin with epoxidized soybean oil (ESO) (mass replacement ratio is 30%:70%);

[0164] 2) In the resin-based electrolyte precursor formula, polylactic acid (PLA) is introduced as a degradable functional polymer. The addition method of PLA is the same as that of functional polymers; the amount of PLA added is 3% of the mass of the resin matrix; the amount of other functional polymers (such as SPEEK) is 2%. It can ensure that the material has the composite functions of ion conductivity (from SPEEK) and degradability (from PLA), while using bio-based epoxidized soybean oil to reduce the proportion of petrochemical raw materials, achieving higher environmental protection and recyclability.

[0165] Example 4

[0166] Recyclability test

[0167] Pyrolysis recovery: The composite material prepared in Example 1 was heated to 500°C in a high temperature furnace to recover carbon fibers and part of the inorganic filler. The results showed that the strength retention rate of the recovered carbon fibers reached 90%, and the composite material could be used to prepare the composite material again.

[0168] Performance Testing

[0169] 1) Conductivity test of the multi-level conductive network prepared in Example 1:

[0170] The surface resistance of the multi-level conductive network measured by a four-probe tester was 0.5Ω / m.

[0171] Electrochemical performance: At 0.1C rate, the initial discharge capacity is 165mAh / g; after 100 cycles, the capacity retention rate is 98%.

[0172] Mechanical properties: The peel strength between the conductive coating and the carbon fiber cloth reaches 5N / cm.

[0173] 2) Ionic conductivity of the resin-based electrolyte precursor prepared in Example 1: At room temperature, the electrical conductivity was measured by an electrochemical impedance spectroscopy method and was 1.5×10-3 S / cm.

[0174] Mechanical properties: tensile strength is 60MPa, elongation at break is 6%.

[0175] 3) Mechanical properties of the multifunctional structural energy storage composite material prepared in Example 1: tensile strength reaches 500 MPa, bending strength is 300 MPa; electrochemical properties: at 1C rate, the initial specific capacity is 155 mAh / g; after 500 cycles, the capacity retention rate is 92%.

[0176] 4) Other tests

[0177] 1. Adhesion test (interface shear strength)

[0178] Test method:

[0179] Standard: ASTM D2344 / D2344M (short beam shear test).

[0180] Purpose: To determine the shear strength of the interface between carbon fiber cloth and resin matrix.

[0181] Test conditions:

[0182] Specimen size: 25mm×6mm×2mm.

[0183] Loading rate: 1mm / min.

[0184] Test environment: room temperature (23℃±2℃), humidity 50%±5%RH.

[0185] Calculation results:

[0186] Interface shear strength (τ) = PA / A, where τ is the interface shear strength (MPa or N / mm 2 ), P is the maximum load (N), A is the shear area (mm 2 ).

[0187] Improved results:

[0188] The interface shear strength between the treated carbon fiber cloth and the resin matrix increased by 20%, from the original 35MPa to 42MPa.

[0189] 2. Ionic conductivity test

[0190] Test standard: ASTM E1461-13 (impedance spectroscopy), measuring the ionic conductivity of resin-based electrolytes.

[0191] Test conditions:

[0192] Sample preparation: Prepare an electrolyte film with a diameter of 20 mm and a thickness of 1 mm.

[0193] Equipment: Electrochemical impedance analyzer (frequency range 1 Hz to 1 MHz).

[0194] Test environment: room temperature (23℃±2℃).

[0195] Calculation results:

[0196] Ionic conductivity (σ) = L / (R·A), where L is the sample thickness, cm; R is the resistance, Ω, and A is the cross-sectional area of ​​the film, cm 2 .

[0197] Test results: After optimization, the ionic conductivity is 1.9×10-3S / cm (at room temperature).

[0198] 3. Electronic conductivity test

[0199] Test standard: GB / T 15662-1995 (four-probe method), to measure the electronic conductivity of the electrode coating.

[0200] Test conditions:

[0201] Sample preparation: Prepare a conductive coating film of 100 mm × 10 mm × 1 mm.

[0202] Test equipment: Four-probe conductivity tester.

[0203] Test environment: room temperature (23℃±2℃).

[0204] Test results: After optimization, the electronic conductivity is 2.8×105S / m.

[0205] 4. Tensile strength test

[0206] Test standard: ASTM D3039 (composite material tensile test), to determine the tensile strength of composite materials.

[0207] Test conditions: sample size: 250mm×25mm×2mm; fixture clamping length: 50mm; loading rate: 2mm / min.

[0208] Test environment: room temperature (23℃±2℃), humidity 50%±5%RH.

[0209] Test results: The tensile strength after optimization is 120MPa.

[0210] 5. Elongation at break test

[0211] Test method: Standard: ISO 527-1 (plastic tensile properties test), determination of the elongation at break of composite materials.

[0212] Test conditions: sample size: 150mm×10mm×2mm; loading rate: 1mm / min; test environment: room temperature (23℃±2℃).

[0213] Test results: The elongation at break after optimization is 6%.

[0214] 6. Thermal stability test

[0215] Test standard: ASTM E1131 (thermogravimetric analysis, TGA), to determine the thermal decomposition temperature and thermal stability of materials.

[0216] Test conditions: heating rate: 10℃ / min; temperature range: 25℃~800℃; environment: nitrogen protection.

[0217] Test results: The material quality retention rate is 95% at 400℃.

[0218] 7. Interface bonding strength test

[0219] Test method:

[0220] Standard: GB / T 2790-1995 (Adhesive shear strength test), tests the bonding strength between the conductive coating and the carbon fiber.

[0221] Test conditions: Sample size: 100 mm × 25 mm × 1 mm; Loading rate: 1 mm / min; Test environment: room temperature (23°C ± 2°C).

[0222] Test results: The coating interface bonding strength is 18MPa.

[0223] 8. Curing time test

[0224] Test method: Standard: ISO 9396 (Epoxy resin curing time), determination of the curing time of fast curing systems.

[0225] Test equipment: Differential Scanning Calorimeter (DSC); Test temperature range: 25°C to 150°C.

[0226] Test results: initial curing time: 1.5 hours (90°C); post-curing time: 1 hour (120°C).

[0227] 5)1. Characterization of multi-level conductive networks

[0228] The results of SEM images show that the conductive network is evenly covered on the surface of carbon fibers without obvious agglomeration; there is no obvious agglomeration of CNTs, and a network structure is formed by the interlacing of CNTs and graphene.

[0229] The TEM image shows that graphene sheets and carbon nanotubes are distributed alternately; MXene sheets are embedded in the pores and tightly combined, and CNTs are microscopically combined with graphene and MXene sheets, which illustrates the hierarchical distribution of different materials in the conductive network.

[0230] Atomic force microscopy (AFM) results show that the coating surface has good uniformity.

[0231] 2. Characterization of resin-based electrolytes

[0232] 1) X-ray diffraction (XRD) analysis

[0233] Purpose of the test:

[0234] Verify the dispersion state between the resin matrix and the ionic liquid and lithium salt; observe whether there is interaction between the crystalline phase and the amorphous phase.

[0235] Testing process:

[0236] The cured resin-based electrolyte film (thickness 0.5-1 mm) was made into a suitable size and tested by X-ray diffractometer. The results showed that:

[0237] 1. No obvious strong diffraction peaks: No obvious diffraction peaks caused by the crystallization of lithium salt or ionic liquid appear in the XRD spectrum, indicating that the lithium salt and ionic liquid are fully dispersed in the resin matrix and are in a basically amorphous state;

[0238] 2. Weakened main peak / shoulder of matrix: With the introduction of ionic liquid and functional polymer, the shoulder peak is significantly weakened or disappears, indicating that there is interaction between molecules and the local ordered structure is destroyed;

[0239] 3. Composite uniformity: The overall amorphous characteristics are shown, proving that the resin-based electrolyte system has good uniformity at the microscopic level and can provide a continuous channel for ion conduction.

[0240] 2) Fourier transform infrared spectroscopy (FTIR) analysis

[0241] Purpose of the test:

[0242] Confirm the interaction between the resin matrix and ionic liquids and lithium salts; verify the successful introduction of functional additives.

[0243] FTIR spectrometer (wave number range 4000~400cm -1 ), and the cured film was subjected to infrared testing.

[0244] The results show that:

[0245] 1. Characteristic peak attribution

[0246] Residual peak of epoxy group (910~930cm -1 ) is greatly weakened after curing, indicating that the curing reaction is sufficient;

[0247] The characteristic peak of -SO3H of sulfonated polyetheretherketone (SPEEK) appears at about 1030-1080cm -1 (symmetric stretching vibration), retaining a relatively obvious intensity, indicating its successful introduction;

[0248] The -CF3 and -SO2 functional groups of the ionic liquid (EMIM-TFSI) are at 1190 and 1450 cm -1 An absorption peak appears at

[0249] Lithium salt (LiPF6) has a weak PF vibration peak (about 840~880cm -1 ).

[0250] 2. Peak position changes

[0251] Slight peak shifts (red / blue shifts) were observed between the hydroxyl, carbonyl, or -SO2 groups of the resin, indicating the presence of hydrogen bonding or ion-dipole interactions between the resin matrix and the ionic liquid / lithium salt;

[0252] The above results showed no obvious missing or additional impurity peaks, indicating that the ionic liquid, lithium salt, functional polymer, etc. were evenly distributed and well combined with the resin matrix.

[0253] 3) Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC)

[0254] Test purpose: To evaluate the thermal stability of resin-based electrolytes and their thermal transition behavior (such as glass transition temperature Tg) to confirm the processing adaptability and operating temperature range of new formulations.

[0255] a) Thermogravimetric analysis (TGA)

[0256] Test process: In a nitrogen atmosphere, heat from room temperature to 600 or 800°C at a heating rate of 10°C / min, and record the curve of sample mass changing with temperature.

[0257] in conclusion:

[0258] 1. Initial decomposition temperature (Td5%)

[0259] A 5% mass loss occurs between 280 and 320 °C, which is mainly attributed to the partial pyrolysis of the organic matrix and the ionic liquid; MXene or SiO2 inorganic fillers can delay the thermal decomposition;

[0260] 2. Main decomposition temperature (Tmax): The maximum weight loss rate peak appears at 350-450°C, corresponding to the skeleton decomposition of epoxy resin and organic polymer;

[0261] 3. Residual carbonization rate: The residual mass is about 20-30% at 600°C, which is slightly higher than that of the pure epoxy system, indicating that the addition of sulfonated polymers or MXene can help improve the carbonization residue;

[0262] 4. Improved thermal stability: Compared with pure resin matrix, resin-based electrolytes have process curing and high-temperature service requirements at 120-150°C).

[0263] b) Differential Scanning Calorimetry (DSC)

[0264] Test process: In a nitrogen atmosphere, the sample was heated twice at a heating rate of 10°C / min, and the change of heat flow with temperature was recorded.

[0265] in conclusion:

[0266] 1. Glass transition temperature (Tg)

[0267] The Tg of the matrix appears in the range of 60-100°C; when ionic liquids or functional polymers are added, the Tg decreases slightly but is still within an acceptable range;

[0268] 2. Residual heat release from curing reaction

[0269] If the curing is incomplete, an exothermic peak will appear in the region of 150-200° C. (curing of residual epoxy groups). In the present invention, there is almost no significant exotherm, indicating that the degree of curing is high.

[0270] The above DSC results show that the formulation of the present invention has sufficient thermal stability, a stable chemical structure in the range of room temperature to 120° C., and can be adapted to rapid curing or use in high temperature environments.

[0271] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a multifunctional structural energy storage composite material, characterized in that: The following steps are involved: mixing carbon nanotubes, graphene, MXene and an organic solvent, and mixing the resulting suspension with a binder and a positive electrode active material to obtain a conductive slurry; The carbon fiber cloth is subjected to plasma treatment to obtain a modified carbon fiber cloth; The conductive slurry is electrospinned on the surface of the modified carbon fiber cloth to form a conductive coating, and then subjected to heat pressing to obtain a multi-level conductive network; Mixing a lithium salt with an ionic liquid to obtain an ionic liquid electrolyte; The ionic liquid electrolyte is mixed with a resin matrix, a functional polymer, a nanofiller and a curing agent to obtain a resin-based electrolyte precursor; Using ANSYS software, topology optimization is performed according to the required mechanical strength and energy storage performance, and according to the optimization results, the multi-level conductive network is compounded with a resin-based electrolyte precursor to obtain a composite precursor; According to the geometric shape obtained by topology optimization, a three-dimensional model of the special-shaped part is established by using SolidWorks, and the three-dimensional model of the special-shaped part is made into a mold by using a CNC processing method; The positive electrode, electrolyte membrane and negative electrode are laid in sequence in a mold, and the composite precursor is injected into the mold by a vacuum-assisted resin transfer molding method, and then cured and molded to obtain a multifunctional structural energy storage composite material.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon nanotube, graphene and MXene is 1 to 3:1 to 3:1; the diameter of the carbon nanotube is 10 to 20 nm, the length is 10 to 30 μm, and the conductivity is greater than 10 4 S / m; the graphene is a single-layer redox graphene with a thickness of <1nm and a side length of 5 to 10μm; the MXene is Ti3C2T x The thickness of the MXene is <2 nm and the sheet diameter is 1 to 5 μm.

3. The preparation method according to claim 1, characterized in that: The binder is polyvinylidene fluoride, and the molecular weight of the polyvinylidene fluoride is 450,000; the power of the plasma treatment is 80-120W, and the time is 5-10 minutes.

4. The preparation method according to claim 1, characterized in that: The electrospinning conditions include: voltage 10-15 kV; collection distance 10-15 cm; slurry flow rate 0.1-0.2 mL / min; The temperature of the hot pressing treatment is 130-160° C., the pressure is 10-15 MPa, and the time is 2-5 hours.

5. The preparation method according to claim 1, characterized in that: The ionic liquid includes 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt; the lithium salt includes lithium hexafluorophosphate; and the mass ratio of the lithium salt to the ionic liquid is 1:5-15.

6. The preparation method according to claim 1, characterized in that: The resin matrix includes bisphenol F epoxy resin; the functional polymer includes sulfonated polyetheretherketone; the nano filler includes nano silicon dioxide; and the curing agent includes polyetheramine curing agent D230 or dicyandiamide.

7. The preparation method according to claim 6, characterized in that: The mass of the functional polymer is 3-6% of the mass of the resin matrix, the mass of the nano filler is 1-3% of the mass of the resin matrix; the mass ratio of the resin matrix to the curing agent is 100:30-50; the mass ratio of the ionic liquid to the resin matrix is ​​0.5-1:

1.

8. The preparation method according to claim 6, characterized in that: When the curing agent is polyetheramine curing agent D230, the curing molding includes: curing at 80-100° C. for 4 hours, and then curing at 120-150° C. for 2 hours.

9. The preparation method according to claim 6, characterized in that: When the curing agent is dicyandiamide, the method further comprises adding a modified imidazole accelerator, wherein the mass of the modified imidazole accelerator is 1.5-3% of the mass of the resin matrix; and the curing molding comprises curing at 120-130° C. for 30 minutes.

10. The multifunctional structural energy storage composite material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Automobile battery box structure design method based on a finite element method

    CN109583058A

  • High-mechanical porous structure electrolyte as well as preparation method and application thereof

    CN118645702A

  • Optimization method and device of hydrogen fuel cell power supply system

    CN119029252A

  • Method of producing graphite-carbon composite electrodes for supercapacitors

    US20090061312A1

  • Fibers, prepreg materials, compositions, composite articles, and methods of producing composite articles

    US20220235191A1

Cited By

  • Multifunctional aerogel fiber based on waste firefighter uniform fabric and preparation method thereof

    CN120211108A